2020
DOI: 10.1002/humu.24076
|View full text |Cite
|
Sign up to set email alerts
|

EpigenCentral: Portal for DNA methylation data analysis and classification in rare diseases

Abstract: Epigenetic processes play a key role in regulating gene expression. Genetic variants that disrupt chromatin‐modifying proteins are associated with a broad range of diseases, some of which have specific epigenetic patterns, such as aberrant DNA methylation (DNAm), which may be used as disease biomarkers. While much of the epigenetic research has focused on cancer, there is a paucity of resources devoted to neurodevelopmental disorders (NDDs), which include autism spectrum disorder and many rare, clinically over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…In other disorders of the epigenetic machinery, a case group clustering out from control subjects using one signature indicates the possible existence of a second overlapping but distinct signature for these subjects. 18 , 22 , 49 We hypothesized that the intermediate clustering of the proximal SRCAP subjects was indicative of a unique DNAm signature associated with these cases, overlapping that of FLHS.
Figure 2 Loss-of-function variants in SRCAP are associated with two distinct but overlapping DNAm signatures based on variant position (A and B) FLHS DNAm signature: (A) principal components analysis (PCA) and (B) heatmap showing clustering of FLHS discovery subjects (n = 4; dark purple), FLHS validation subjects (n = 4; light purple), proximal SRCAP discovery subjects (n = 5; dark orange), proximal SRCAP validation subjects (n = 4; light orange), distal SRCAP subjects (green) and discovery control subjects (n = 35; blue) using DNAm values at 464 CpG sites in the FLHS DNAm signatures.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other disorders of the epigenetic machinery, a case group clustering out from control subjects using one signature indicates the possible existence of a second overlapping but distinct signature for these subjects. 18 , 22 , 49 We hypothesized that the intermediate clustering of the proximal SRCAP subjects was indicative of a unique DNAm signature associated with these cases, overlapping that of FLHS.
Figure 2 Loss-of-function variants in SRCAP are associated with two distinct but overlapping DNAm signatures based on variant position (A and B) FLHS DNAm signature: (A) principal components analysis (PCA) and (B) heatmap showing clustering of FLHS discovery subjects (n = 4; dark purple), FLHS validation subjects (n = 4; light purple), proximal SRCAP discovery subjects (n = 5; dark orange), proximal SRCAP validation subjects (n = 4; light orange), distal SRCAP subjects (green) and discovery control subjects (n = 35; blue) using DNAm values at 464 CpG sites in the FLHS DNAm signatures.
…”
Section: Resultsmentioning
confidence: 99%
“…In other disorders of the epigenetic machinery, a case group clustering out from control subjects using one signature indicates the possible existence of a second overlapping but distinct signature for these subjects. 18,22,49 We hypothesized that the intermediate clustering of the proximal SRCAP subjects was indicative of a unique DNAm signature associated with these cases, overlapping that of FLHS.…”
Section: Study Cohortmentioning
confidence: 99%
“…Alterations in DNA methylation patterns are implicated in imprinting disorders and diseases of short tandem repeat (STR) expansions. The application of DNA methylation analyses has been successful in identifying molecular diagnoses in neurodevelopmental disorders where clinical microarray and other conventional genetic testing have been non-diagnostic (Aref-Eshghi et al, 2019;Turinsky et al, 2020). LaCroix et al (2019) investigated cases of Baratela-Scott syndrome (BSS) (MIM: 615777) and identified hypermethylation of exon 1 of XYLT1 associated with a GGC expansion and gene silencing.…”
Section: Integrating Multi-omics Datamentioning
confidence: 99%
“…One method that has been successfully applied to address this issue is to run multiple signatures as a panel and interpret results together. 31,32 When sample sizes are low, potentially resulting in a dearth of CpGs meeting statistical thresholds for significance, exploratory analyses may be performed by relaxing the statistical threshold. This can answer the question of whether true differential methylation patterns likely exist but are being obscured by poor statistical power.…”
Section: Sample Sizementioning
confidence: 99%